FACILITY MANAGEMENT OF WATERFALL TOURISM OBJECTS SEVEN LEVELS OF BATANG KOBAN IN KUANTAN SINGINGI DISTRCIT - Valensi Nadia Putri; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
One of the mainstay attractions in Kuantan Singingi Regency, Batang Koban Seven Level Waterfall Toursim Object in located in Lubuk Ambacang Vilagge, Hulu Kuantan District. This study aims to determine how the management of facilities at the Seven Levels Batang Koban Waterfall Tourism Object. Management has four functions, namely planning, organizing, implementing, supervising. Facilities are supporting facilities that can create a sense of fun accompanied by convenience and fulfillment of tourist needs in enjoying the tourism product offered. People travel to a place for serveral reasons, one of which is the availability of supporting facilities affects the deveploment of the number of tourists at the Batang Koban Seven Level Waterfall attraction. Facilities are not the main factor that can stimulate tourist arrivals to a tourist destination, but the absence of facilities can prevent tourists from enjoying tourist attractions. This study uses a qualitative method with a descriptive approach, the subject of this research is the Head of Tourism Destinations, Head of section for management of tourism destinations, Head of tourism bussines service and section, Adyatama tourism and creative economy of the tourism and culture office of Kuantan Singingi Regency, and Pokdarwis. Data collection is done by interview, observation, and documentation. Data analysis in this study was carried out by data reduction, data presentation, and drawing conclusions. Keywords: management, facilities and the batang koban seven-story waterfall